Essential oil from Chenopodium ambrosioides L.: secretory structures, antibacterial and antioxidant activities - Santiago, Juliana Andrade (2016)
The aim of this study was to evaluate the antibacterial and antioxidant activities of essential oil from Chenopodium ambrosioides L. and to determine its secretory structures. The essential oil was extracted through the hydrodistillation technique using a modified Clevenger apparatus (2 hours) and chemically characterized by GC/MS and GC-FID. The antioxidant activity was determined by monitoring the reduction of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and by the oxidation of the β-carotene/linoleic acid system. The evaluation of antibacterial activity was performed by the agar cavity diffusion technique using the microorganisms Staphylococcus aureus, Listeria monocytogenes, Escherichia coli and Salmonella Cholerasuis. The characterization of trichomes was accomplished by Scanning Electron Microscopy (SEM) and histochemical tests with Nadi and Sudan IV reagents. The antioxidant activity demonstrated by the β-carotene/acid linoleic test, with IC50 = 455.7 µg mL-1. This oil also presented antibacterial activity for both Gram-negative and Gram-positive bacteria. The minimal inhibitory concentration ranged 62.5 to 250 µL mL-1. The presence of terpenes in the glandular trichomes was observed, suggesting that the essential oil is secreted by these structures.